2008
DOI: 10.1063/1.3041634
|View full text |Cite
|
Sign up to set email alerts
|

Determining the optimum pentacene channel thickness on hydrophobic and hydrophilic dielectric surface

Abstract: We report that the optimum pentacene channel thickness is dependent on the surface energy state of its dielectric substrate. Pentacene thin-film transistor (TFT) with hydrophobic substrate displays a peak linear mobility at an optimum channel thickness of 50nm, below or above which the linear mobility decreases. In contrast, the linear mobility of the TFT with hydrophilic substrate monotonically increases until the channel thickness decreases to 15nm. According to atomic force microscopy of 15-nm-thin pentacen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…The I D was increased with decreasing film thickness. Although this tendency agrees to the reported result [6] that I D increases with decreasing the thickness of the pentacene fabricated on the SiO 2 , it is not clarified in our experiment that the reason of the dependency of I D on the pentacene thickness is due to its grain size. The grain size of pentacene film with 50 nm thickness is larger than that with 3 nm thickness.…”
Section: Experimental Methodssupporting
confidence: 40%
See 1 more Smart Citation
“…The I D was increased with decreasing film thickness. Although this tendency agrees to the reported result [6] that I D increases with decreasing the thickness of the pentacene fabricated on the SiO 2 , it is not clarified in our experiment that the reason of the dependency of I D on the pentacene thickness is due to its grain size. The grain size of pentacene film with 50 nm thickness is larger than that with 3 nm thickness.…”
Section: Experimental Methodssupporting
confidence: 40%
“…And also it is important to improve the driverbility from a viewpoint of current drive of organic light emitting diode (OLED) displays. The characteristics of pentacene TFT has been examined [1,2,3,4,5,6,7]. The influence of pentacene thickness on TFT performance were reported: The bias-stress effect of OTFT has a close relation with the pentacene thickness ranging from 10 to 80 nm [5] and field-effect mobility of OTFT is affected by pentacene thickness ranging from 15 to 100 nm [6].…”
Section: Introductionmentioning
confidence: 99%
“…Even the few studies that have used hydrophobic dielectrics do not discuss the role played by the same in determining the optimum thickness [17,19]. To our knowledge only Mun et al have compared the optimum thickness on the hydrophilic and hydrophobic substrates [15] where they have shown maximum mobility for higher thickness on the hydrophobic substrate as compared to that on hydrophilic substrate. They attributed the difference in optimum thickness to the difference in initial growth mode on hydrophilic and hydrophobic substrates.…”
Section: Introductionmentioning
confidence: 92%
“…As mentioned before, it has been discussed in the literature that nucleation density and grain size of organic semiconductors depend mainly on the surface energy conditions of the dielectric surface [9,15,16]. As molecular ordering is reported to improve due to the increased moleculeemolecule interaction of organic semiconductors on hydrophobic surfaces, it is essential to determine the optimum thickness of the active layer on such hydrophobic dielectrics and to understand the influence of the hydrophobic dielectrics in deciding the optimum thickness to obtain higher mobility and threshold voltage stability.…”
Section: Introductionmentioning
confidence: 99%
“…Jurchescu et al [8] showed that impurities and defect states in pentacene lead to lower field-effect mobility. In addition, OTFT performance is dependent on the dielectric-semiconductor interface which is affected by preparation of gate dielectric [9][10][11], the growth of pentacene, and the channel thickness [12]. In this paper, we studied the effect of pentacene evaporation rate and purity on the performance of fully-dry, low-voltage OTFTs with total thickness of gate dielectric of ~ 20 nm.…”
Section: Introductionmentioning
confidence: 99%